Kirigami electrodes of conducting polymer nanofibers for wearable humidity dosimeters and stretchable supercapacitors. Issue 15 (7th April 2021) - Diao, Yifan; Woon, Reagan; Yang, Haoru; Chow, Alina; Wang, Hongmin; Lu, Yang; D'Arcy, Julio M.
Abstract : Nanofibrillar Kirigami electrodes enable superior sensitivity in humidity sensors and state-of-the-art energy density in supercapacitors. Abstract : Kirigami, the art of paper cutting, presents a promising approach for maximizing stretchability in planar sheets which is of paramount importance for the next-generation of wearable smart electronics. Current state-of-the-art Kirigami-based devices suffer from thin-film electrodes characterized by a limited surface area and poor electronic performance. Here, we introduce a synthetic strategy that affords layer-by-layer control for depositing nanofibrillar conducting polymer composite coatings possessing a high packing density and high surface area. A Kirigami-based humidity dosimeter developed using our PEDOT nanofibers exhibits superior sensitivity over the commercial product PEDOT:PSS. This wearable dosimeter, when stretched by 200%, exhibits a 40% resistance change within seconds (<2 s) after exposure to a new humidity level. A PPy/PEDOT composite film is produced by sequential deposition of two different conducting polymer nanofibers resulting in a superior electrode for developing stretchable supercapacitors. Our electrochemical capacitors exhibit a synergistic effect that leads to a state-of-the-art energy density (115 μW h cm −2 at 1 mA cm −2 ) and an extended stretch cycle capacitance stability (85% of original capacitance is retained after 300 stretching cycles of 100%).